Fuel Subsidy Removal and the Political Sagacity of the Tinubu Administration: Implications and Coping Mechanisms - Aligbe, Bendrix Abdullah; Momoh, Mariam Millie (Kashere Journal of Politics and International Relations, 2023)
Despite the humongous amount of money the Nigerian government spends on fuel subsidy, the situation has not translated to an improved standard of living for the people. The reason being that our collective patrimony is not being efficiently and effectively utilized to achieve developmental goals. Consequently, a poor health system and economy solely dependent on crude oil export for its government revenue has posed serious problems to the economy. In the midst of this, the Tinubu-led government announced the full deregulation of the downstream oil sector on inauguration in May 29, 2023 in the country and full removal of subsidy on petroleum products. This paper therefore, examines the effects of the fuel subsidy removal on the Nigerian poor and its overall benefits to the Nigerian economy, using descriptive research design method. The paper, however noted that while the poor will suffer more in the form of higher transport fares, high cost of living, high cost of running business, increase in lack/need, and income versus expenses, subsidy removal is in the overall interest of the whole economy as funds will be channeled to improving infrastructural amenities, especially in the healthcare, education and transport sectors. The paper then recommends transparent honesty on the part of the government in expending the funds saved from fuel subsidy removal, and government should give more attention to refining our petroleum here in Nigeria by fixing her refineries.